Body image perception, well-being and creativity in Chinese university students: The necessity for a novel course of medical aesthetics - Xiangyu Wang; Tianjing Wang; Leyi Fu; Feng Yun; Fan Qu; Fangfang Wang (PLoS ONE, 2025)
Objective Body image perception significantly impacts university students’ well-being and potentially their creativity. Traditional aesthetic education often neglects direct engagement with body image concerns. To address this gap, we developed an innovative general education course, Aesthetics in Traditional Chinese Medicine and Western Medicine, integrating medical aesthetics with multidisciplinary perspectives. This study aimed to optimize the curriculum of our course with evidence-based insights by exploring the relationship among students’ self-perception of physical appearance, well-being, and creative self-efficacy. Methods A cross-sectional study was conducted among 328 students at Zhejiang University in December 2024. Participants completed validated scales: Negative Physical Self Scale (NPSS), Objectified Body Consciousness Scale (OBCS), WHO-5 Well-Being Index (WHO-5), and Creative Self-Efficacy scale (CSE). Demographic data and course enrollment intention were also collected. Results Significant intercorrelations were observed among NPSS, OBCS, WHO-5, and CSE scores. These associations were further influenced by demographic and academic factors, including sex, age, grade, and major. Specifically, female students exhibited higher levels of self-objectification, while lower-year students reported more negative self-perception of physical appearance. Moreover, Life Sciences & Medicine students demonstrated a greater tendency toward negative self-perception, low psychological well-being level, and decreased creative self-efficacy, compared to peers in other disciplines. Conclusion Based on these findings, we propose refining the course with targeted educational interventions, fostering positive body image perception, and addressing the specific needs of identified student groups—particularly medical students—to cope with these challenges.